Stress in Medical Residency: Cognitive Work Analysis and a Literature Review. Issue 1 (June 2013) - Nystrom, Daniel T.; Rantanen, Esa M.; Lintern, Gavan
Resident physicians endure substantial amounts of stress to acquire the necessary skills and knowledge to become competent, certified physicians. Multiple factors that contribute to high levels of stress in different areas of the healthcare domain have been identified, but stress continues to be a major problem despite this knowledge and efforts to reduce it. This study employed the framework of Cognitive Work Analysis to systematically review and organize relevant research literature to gain a holistic understanding of resident stress. The result of our work is a representation of resident physicians' work domain with relevant literature investigating resident stress associated to each area of the representation. The representation provides an organizational structure to examine sources of stress that have been heavily investigated in the resident physicians work domain and identifies areas that lack systematic research.